MODEL PEMBELAJARAN DIRECT INSTRUCTION TERHADAP HASIL BELAJAR AKUNTANSI - Rijal Lubis, Khairunnisa (JURNAL PENDIDIKAN IPS, 2020)
The learning model refers to the approach that will be used, including the learning objectives, the stages in learning activities, the learning environment, and classroom management. Direct Instruction Learning Model is a direct learning model specifically designed to support student learning processes related to declarative knowledge and well-structured procedural knowledge that can be taught with a pattern of activities that are step by step, step by step. The formulation of the problem in this study is "Are the learning outcomes of students who learn using the Direct Instruction Learning Model higher than the learning outcomes of students who learn to use the Conventional Model. The results of data analysis in this study obtained t count 40,2291 and t table 2,0042 so that t count> t table (40,2291> 2,0042), this shows that the hypothesis that the author has specified in this study is acceptable. That is, the learning outcomes of students who learn using the Direct Instruction method are higher than the learning outcomes of students who learn using conventional methods. In line with these conclusions, researchers suggested that accounting teachers apply Direct Instruction learning methods in the teaching and learning process, especially on accounting subjects.